Distinct features and validation of δ⋇-algebras: an analytical exploration - Muralikrishna, Prakasam; Hemavathi, Perumal; Vinodkumar, Raja; Chanthini, Perumal; Palanivel, Kaliyaperumal; Edalatpanah , Seyyed Ahmad (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This research introduces the concept of a δ⋇- algebra, a unique structure in the field of abstract algebra. The study aims to explore the defining features and distinct properties of δ⋇-algebras, distinguishing them from other algebraic systems and examining their interrelations with other types of algebras. Methods: The methodology includes the formal definition and characterization of δ⋇-algebras, a comparative analysis with the existing algebraic structures, and an exploration of their interconnections. An algorithm is developed to verify whether a given structure meets the conditions of a δ⋇-algebra. Results: The results reveal that δ⋇-algebras possess unique properties not found in other algebraic systems. The comparative study clarifies their distinctive place within the algebraic landscape and highlights significant interrelations with other structures. The verification algorithm proves effective in identifying δ⋇-algebras, providing a systematic approach for further study. Conclusions: In conclusion, δ⋇-algebras represent a significant addition to abstract algebra, offering new theoretical insights and potential for future research. The study’s findings enhance the understanding of algebraic systems and their interconnections, opening new avenues for exploration in the field.